Peran Kepemimpinan Digital Dedi Mulyadi dalam Pengembangan Talenta Digital melalui Program JIDA 2025 di Jawa Barat - Silvy Novianty; Aisyah Aulia; Assyfa Futri Ananta; Jauzari Helmi; Edy Akhyari (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Digital transformation has brought about major changes in leadership patterns, especially in the public sector. In this context, digital leadership is key for leaders to drive innovation and adaptation to technological developments. However, the success of digital leadership is also inseparable from democratic leadership values that emphasize participation, openness, and collaboration. The synergy between these two values is an important foundation for building an effective and humanistic leadership style in the digital age. This study aims to analyze the role of Dedi Mulyadi's digital leadership in developing digital talent through the 2025 Jabar Istimewa Digital Academy (JIDA) program in West Java. The approach used is qualitative with a literature study method, sourced from 14 scientific journals and three official news reports. The results of the study show that Dedi Mulyadi applies a visionary, adaptive, and collaborative digital leadership style. Democratic values are also evident through a participatory approach that involves the community, educational institutions, and the industrial sector in the implementation of the JIDA 2025 program. This program has proven to strengthen digital literacy, expand access to technology training, and improve the readiness of West Java's human resources in facing the challenges of the digital economy. Thus, digital leadership combined with democratic principles plays an important role in realizing inclusive, competitive, and sustainable human resource development in the era of digital transformation.